Effects of sprint interval training on body composition and anthropometry in recreational long-distance runners - Kamil Michalik; Natalia Danek; Iwona Wierzbicka-Damska (Kazimierz Wielki University, 2018)
Background The purpose of the study was to investigate the anthropometric effects of sprint interval training (SIT) protocol on body composition and the circumferences of selected body segments in recreational long-distance runners. Methods A sample of 17 participants was randomized to receive sprint interval training (SIT; n=8) and continuous endurance training (CONT; n=9). CONT trained three to four times per week while SIT executed two interval training sessions and one continuous training session per week. The present study involved 4 to 8 min bouts in one interval training unit, whereas the control group trained from 40 to 150 min (40-50km per week). Training duration was 8 weeks. Pre- and post-intervention measures of body composition were determined by near-infrared interactance. Circumferences (chest, waist, calf and thigh of the dominant leg) were recorded. Results No decrease in body fat mass was observed in SIT. Additionally, post-intervention waist circumference significantly decreased (p